ENGLISH SUBJECT ON ENGLISH FOR SPECIFIC PURPOSES (ESP) IN VOCATIONAL SCHOOLS - Fadlia Fadlia; Evi Zulida; Surya Asra; Rahmiati Rahmiati; Allif Syahputra Bania (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2020)
This study aimed to analyze the English subject in two vocational schools in Kota Langsa based on English for Specific Purposes (ESP) approach and how it was implemented in the classroom. This study applied a descriptive qualitative method. The two vocational schools involved in the research are Hotel Hospitality Management and Maritime Fishing Vessel Engineering. The data were gained from the teachers and students by conducting observation, interview, Focus Group Discusssion (FGD), and document analysis of syllabus and teaching materials. The data were analyzed by comparing the real condition of teaching-learning process and the ideal condition based on ESP approach. The finding showed that the two schools used General English (GE) frequently rather than ESP on English subject. Despite the common use of GE in these two schools, they had the option to adjust their English subject into ESP standard. One school had the ESP subject called English for Maritime and another school chose Mandarin subject as the option. As a result, the school only had GE for English subject. Thus, the English subject was taught and designed as English for General Purposes rather than English for Specific Purposes.